2021
DOI: 10.1177/21925682211011444
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Surgery for Sacral Chordoma and Impact of Complications: A Report of 50 Consecutive Patients With Long-Term Follow-Up

Abstract: Study Design: Retrospective case series. Objective: To determine predictive factors of overall survival (OS) and local recurrence (LR), report complications, and assess the impact of complications on survival, recurrence, and function in patients undergoing en bloc resection of sacral chordoma. Methods: This retrospective case series was obtained from a prospective database (1995-2016). All patients underwent en bloc resection of sacral chordoma. Demographic, perioperative, and complication data were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…Consistent with our study, several studies indicated that surgery with negative margins was still the preferred treatment to achieve local control and a well longterm outcome [37]. Besides, a retrospective cohort study by Zuckerman et al [38] certified that although complete en-bloc surgical resection with negative margins was not statistically significantly correlated with overall survival, it was significantly associated with lower levels of local recurrence in patients with sacral chordoma. More studies are still needed in the future to verify the prognostic importance of surgical types for spinal and pelvic chordoma.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our study, several studies indicated that surgery with negative margins was still the preferred treatment to achieve local control and a well longterm outcome [37]. Besides, a retrospective cohort study by Zuckerman et al [38] certified that although complete en-bloc surgical resection with negative margins was not statistically significantly correlated with overall survival, it was significantly associated with lower levels of local recurrence in patients with sacral chordoma. More studies are still needed in the future to verify the prognostic importance of surgical types for spinal and pelvic chordoma.…”
Section: Discussionsupporting
confidence: 90%
“…If the tumor excision at higher than S1 level the motor dysfunction can occur. (8) In our case the sacral above the S2 level is preserved, therefore the motor function is preserved and there is only a slight dysfunction in bladder and bowel.…”
Section: Discussionmentioning
confidence: 45%
“…While the sacrum represents the keystone of the pelvis, sacrectomy is often the treatment of choice to provide the greatest chance of progression-free and overall survival for patients with primary malignant bone tumors of the sacrum. [2][3][4][5]18 After midsacral amputation, although a significant remnant of the sacral ala remains, structures such as the sacrotuberous and sacrospinous ligaments are removed, diminishing the stability of the sacropelvic interface, resulting in insufficiency fractures. 7,14 To address this problem, we added motion-sparing standalone intrapelvic fixation as an adjunct to traditional midsacrectomy, while avoiding the morbidity of instrumenting into the mobile lumbar spine.…”
Section: Discussionmentioning
confidence: 99%
“…1 Various studies have supported en bloc sacral resection because it allows for the greatest chance of progression-free and overall survival for patients with primary malignant bone tumors of the sacrum. [2][3][4][5] As such, sacrectomy is often the treatment of choice, frequently in conjunction with adjuvant or neoadjuvant chemotherapy and radiation. 2,3,6 Stability of the sacropelvic connection relies on both the S1 body and the S1 ala with greater emphasis on the S1 than the S2.…”
mentioning
confidence: 99%